PEMBENTUKAN PORTOFOLIO OPTIMAL PADA BEBERAPA SAHAM YANG MASUK PADA INDEKS PEFINDO25 YANG TERCATAT DI BURSA EFEK INDONESIA - Sa?diyah, Chalimatuz (Department of Management, 2015)
This study aims to determine the stock that form the optimal portofolio and the proportion of funds invested and determine the rate of return and level of risk of the optimal portofolio of stocks that, is formed in the PEFINDO25 index listed on Indonesian Stock Exchange, in the study period at August 2011 to July 2013. The method of analysis used in this study is a single index model method and sampling techniques using purposive sampling. Based on the results of data analysis stocks that form the optimal portofolio in PEFINDO25 index in the period at August 2011 ? July 2013, obtained three stocks included in the optimal portofolio members. The share are accompanied by the proportion of investment funds is BISI (BISI International Tbk) 48,4379%, GZCO (Gozco Plantations Tbk) 31,3017%, HRUM (Harum Energy Tbk) 20,2604%,. The stocks are result yield rate of return on a portofolio that will get investors at 0,151% and the portofolio risk level of 0,003%.